Pengaruh Disiplin Terhadap Kinerja Pegawai - Azis Rachman; Titin Dunggio; Darman; Ayu Anastasya Rachman (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
By observing 100 samples of employees at Bina Mandiri University Gorontalo, this study tries to explain the effect of discipline on employee performance at Bina Mandiri University Gorontalo. The data were analyzed using PLS-SEM technique through SMARTPLS software version 4. The samples used were employees and lecturers of Bina Mandiri Gorontalo University by distributing them in an online questionnaire through google form. The results show that Discipline significantly affects employee performance, with a TStatistic value of 9.199 and P Values of 0.000.